Analysis of Influencing Factors and Strategies to Increase MSME Income in Muara Bulian District - Aprilya, Agnes Monica; Tan, Syamsurijal; Syuhada, Siti (LPPM Universitas Jambi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic development, including in Muara Bulian District, Batang Hari Regency. This study aims to analyze the socioeconomic conditions of MSME actors, identify factors that influence income, and formulate strategies to increase income. The research uses a quantitative descriptive approach and verification method. Data were collected through questionnaires distributed to 96 respondents selected using the Slovin formula. Data analysis techniques used include descriptive analysis, multiple linear regression, and SWOT analysis. The results showed that the socioeconomic conditions of MSME actors are dominated by productive age groups (30–49 years old), with the majority having higher education (Bachelor’s degree). Simultaneously and partially, variables of business capital, education level, number of family members, and labor have a positive and significant effect on income. Business capital is the most dominant influencing factor with a beta value of 0.533. Based on SWOT analysis, the position of MSMEs is in Quadrant I, which supports an aggressive strategy. The recommended strategies include increasing production capacity, optimizing digital marketing, and strengthening partnerships with government and financial institutions.